Association Between Postnatal Steroid Use and Long-term Neurodevelopmental Impairment : A Systematic Review - Deskafiani Putri; Firman Syahbana (The International Journal of Medical Science and Health Research, 2026)
Introduction: Postnatal systemic corticosteroids are used to prevent or treat bronchopulmonary dysplasia (BPD) in preterm infants, but concerns persist regarding their association with long-term neurodevelopmental impairment (NDI). This systematic review synthesizes evidence on the association between postnatal steroid use (dexamethasone and hydrocortisone) and long-term neurodevelopmental outcomes. Methods: A systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria: neonatal exposure to systemic postnatal corticosteroids, comparison groups, neurodevelopmental outcomes assessed at ≥12 months corrected age, and RCT or high-quality observational design. Data extraction covered study design, population, steroid regimen, neurodevelopmental outcomes, follow-up timing, association results, and confounding factors. A total of 80 studies were included. Results: Early dexamethasone (<7-8 days) consistently increased cerebral palsy (CP) risk (RR 1.77, 95% CI 1.21-2.58; Doyle et al., 2021). Late dexamethasone (≥7 days) showed no significant CP increase. Early hydrocortisone did not significantly increase CP (RR 1.06, 95% CI 0.67-1.67; Morris et al., 2019) and improved survival without moderate-severe NDI in some analyses. Late hydrocortisone showed neutral neurodevelopmental effects in large RCTs at 2 years and school age. Dose-response relationships were observed for both agents. Gestational age and baseline BPD risk modified treatment effects. Discussion: Apparent contradictions in the literature are reconciled by considering timing of initiation (early vs late), steroid type (dexamethasone vs hydrocortisone), cumulative dose, historical regimens versus current low-dose protocols, confounding by indication, competing mortality risk, and effect modification by gestational age and BPD risk. Early dexamethasone is consistently harmful, while hydrocortisone appears predominantly neutral but with dose-dependent signals. Conclusion: Early dexamethasone should be avoided. Late dexamethasone and hydrocortisone have more favorable profiles but require careful patient selection. The benefit-risk balance is most favorable for extremely preterm infants at highest BPD risk. Further school-age follow-up studies are needed.